Phyto-pharmacological Investigations of Leaves of Cissus trifoliata (L.) (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Repeated chromatographic separation and purification of dichloromethane soluble partitionate of methanol extract of leaves of Cissus trifoliata (L.) yielded a total of four compounds, namely β-sitosterol (1), β- sitostenone (2), epifriedelanol (3) and friedelin (4). The structures of the isolated chemical compounds were established by high field nuclear magnetic resonance (NMR) analyses, comparison with previously published data and co-TLC with authentic samples, whenever possible. Compounds 1-4 appeared to be the first time they were identified in this plant species. The methanol extract of C. trifoliata was assessed for central and peripheral analgesic activities by tail immersion and acetic acid-induced writhing reflex methods, respectively. The crude extract demonstrated significant central and peripheral analgesic efficacy at 200- and 400-mg/kg b.w. in mice model. The general toxicity of the extractives was assessed through a brine shrimp lethality bioassay, where the ethyl acetate (LC50=0.88 μg ml–1) and dichloromethane (LC50=0.93 μg ml–1) soluble fractions demonstrated considerable activity. The crude extract at 400 mg/kg (b.w.) also displayed significant antidiarrheal activity, whereas its dichloromethane soluble fractions exhibited moderate thrombolytic activity.Dhaka Univ. J. Pharm. Sci. 21(1): 69-75, 2022 (June)